Application of multi-representational discourse model to improve students' communication skills - Norjanah Norjanah; Jumrodah Jumrodah; Abdul Gofur (Journal of Research in Instructional, 2025)
Students who have good communication skills tend to find it easier to understand the material, collaborate with classmates, and complete assignments. Communication skills must be established in students. Learning is not optimal without good communication (good interaction between educators and students). The research on applying the multi-representational discourse (MRD) learning model. This study aimed to explore how this model can improve students' communication skills. The method used in this study was classroom action research. This study was conducted on grade XI students at MAN Kota Palangka Raya with 36 respondents. The data analysis technique used is a quantitative analysis technique to compare student activities during the cycle. The results showed an increase in students' communication skills using MRD learning. The MRD model encourages students to discuss and exchange opinions actively, improving their ability to communicate verbally and non-verbally. The results showed increased students' communication skills, especially in expressing opinions, discussing, making presentations, and asking questions. The use of models that involve active interaction between students, such as group discussions, can have a positive impact on the learning process.